Helsinki Stroke Model Is Transferrable With “Real-World” Resources and Reduced Stroke Thrombolysis Delay to 34 min in Christchurch - Wu, Teddy Y.; Coleman, Erin; Wright, Sarah L.; Mason, Deborah F.; Reimers, Jon; Duncan, Roderick; Griffiths, Mary; Hurrell, Michael; Dixon, David; Weaver, James; Meretoja, Atte; Fink, John N. (Frontiers in Neurology, 2018)
Background: Christchurch Hospital is a tertiary hospital in New Zealand supported by 5 general neurologists with after-hours services provided mainly by onsite non-neurology medical residents. We assessed the transferability and impact of the Helsinki Stroke model on stroke thrombolysis door-to-needle time (DNT) in Christchurch Hospital. Methods: Key components of the Helsinki Stroke model were implemented first in 2015 with introduction of patient pre-notification and thrombolysis by the CT suite, followed by implementation of direct transfer to CT on ambulance stretcher in May 2017. Data from the prospective thrombolysis registry which began in 2012 were analysed for the impact of these interventions on median DNT. Results: Between May and December 2017, 46 patients were treated with alteplase, 25 (54%) patients were treated in-hours (08:00 – 17:00 non-public holiday weekdays) and 21 (46%) patients were treated after-hours. The in-hours, after-hours and overall median (interquartile range) DNT were 34 (28-43), 47 (38-60) and 40 (30-51) minutes. The corresponding times in 2012-2014 prior to interventions were 87 (68-106), 86 (72-116) and 87 (71-112) minutes, representing median DNT reduction of 53, 39 and 47 minutes respectively (p-values < 0.01). The interventions also resulted in significant reductions in the overall median door-to-CT time (from 49 to 19 minutes), CT-to-needle time (32 to 20 minutes) and onset-to-needle time (168 to 120 minutes). Conclusion: The Helsinki Stroke model is transferrable with real-world resources and reduced stroke DNT in Christchurch by over 50%.